2021
DOI: 10.1002/jum.15708
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Ultrasound Versus Magnetic Resonance Imaging for Assessing Myometrial Infiltration in Endometrioid Low Grade Endometrial Cancer

Abstract: Objective-To compare the diagnostic accuracy of transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) for assessing myometrial infiltration (MI) in patients with low grade endometrioid endometrial cancer.Methods-Observational prospective study performed at a single tertiary care center from 2016 to 2020, comprising 156 consecutive patients diagnosed by endometrial sampling as having an endometrioid grade 1/grade 2 endometrial cancer. TVS and MRI were performed prior to surgical staging for assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…1,5 Recent studies reported for Karlsson's method sensitivity from 56.3% to 86.8%, specificity from 64.4% to 76.4%, PPV from 62.8% to 83.6%, NPV from 70% to 71.2% and overall accuracy 68.1%. 5,6,19,21 Besides, current study did not find statistical differences between Gordon's and Karlsson's method. Although both TVUS objective calcula-tions, Gordon's and Karlsson's method, had similar accuracy, the approach published by Gordon et al have better sensitivity and accuracy in preoperative assessment of MI in EC.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…1,5 Recent studies reported for Karlsson's method sensitivity from 56.3% to 86.8%, specificity from 64.4% to 76.4%, PPV from 62.8% to 83.6%, NPV from 70% to 71.2% and overall accuracy 68.1%. 5,6,19,21 Besides, current study did not find statistical differences between Gordon's and Karlsson's method. Although both TVUS objective calcula-tions, Gordon's and Karlsson's method, had similar accuracy, the approach published by Gordon et al have better sensitivity and accuracy in preoperative assessment of MI in EC.…”
Section: Discussioncontrasting
confidence: 63%
“…In analysed studies diagnostic performance for MRI reached sensitivity from 70% to 92.6%, specificity from 71% to 95%, PPV from 65% to 92.2%, NPV from 70% to 98%, and overall accuracy from 74% to 89%. [7][8][9][10][12][13][14][15][20][21][22] We have shown that two imaging modalities (contrast-enhanced MRI and TVUS) perform equally well in the assessment of MI, differences in the performance were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact might bias the results and could overestimate the actual diagnostic accuracy of both TVS and MRI in low‐risk cases, where preoperative assessment of myometrial and cervical invasion makes sense from the point of view of the gynecologic oncologist. Some recent studies focusing of low risk histology cases have shown that TVS and MRI have similar diagnostic performance for identifying myometrial infiltration in such cases 6–8 …”
mentioning
confidence: 99%